2016
DOI: 10.1007/978-3-319-49094-6_17
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Using Dependency Knowledge at Integration Testing

Abstract: Abstract. In software system development, testing can take considerable time and resources, and there are numerous examples in the literature of how to improve the testing process. In particular, methods for selection and prioritization of test cases can play a critical role in efficient use of testing resources. This paper focuses on the problem of selection and ordering of integration-level test cases. Integration testing is performed to evaluate the correctness of several units in composition. Further, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In this article, we quote some relatively simple BPEL workflow applications to test the effectiveness of our proposed method, and the results also show that our improved method is a new way worth trying. In the following exploration, we need to further optimize the algorithm to achieve a trade-off between program detection effectiveness and work efficiency [37]. Secondly, in the quantitative calculation of test case importance, we assume that all activities can be modified or affected; and assume that errors or modifications of an activity will be 100% propagated to all activities that directly and indirectly depend on this activity in the activity dependence graph.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we quote some relatively simple BPEL workflow applications to test the effectiveness of our proposed method, and the results also show that our improved method is a new way worth trying. In the following exploration, we need to further optimize the algorithm to achieve a trade-off between program detection effectiveness and work efficiency [37]. Secondly, in the quantitative calculation of test case importance, we assume that all activities can be modified or affected; and assume that errors or modifications of an activity will be 100% propagated to all activities that directly and indirectly depend on this activity in the activity dependence graph.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that automating the testing process itself is in general a costly process and investment. Therefore, a careful cost-benefit analysis and evaluating where and when test automation can pay off, particularly in industrial contexts, is crucial [20], [21]. For instance, if a test is only executed once then perhaps investing to build an automatic test framework may not be worth the effort and cost.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Paying no attention to dependencies between test cases may lead to sequential failure of them and thereby waste of testing resources. In [13] we showed that the dependencies among test Derive similarity vectors from the Doc2Vec model Test specifications (*. docx files)…”
Section: Background and Related Workmentioning
confidence: 99%